Pilot-scale direct UV-C photodegradation of pesticides in groundwater and recycled wastewater for agricultural use. Issue 5 (October 2021) - Ferhi, S.; Vieillard, J.; Garau, C.; Poultier, O.; Demey, L.; Beaulieu, R.; Penalva, P.; Gobert, V.; Portet-Koltalo, F.
Abstract: Pesticides widely used for intensive agriculture may leach to groundwater and pose problems to drinking water and irrigation. UV-C disinfection systems (UV-DS) for water disinfection can be used also for the abatement of organic micropollutants. A pilot-scale continuous flow-through UV-DS system was evaluated for its degradation efficiency of atrazine (ATR), malathion (MAL) and glyphosate (GLY) from 40 L water. Groundwater used to irrigate potato fields and recycled wastewater used to wash potatoes were treated without catalysts to avoid any toxicity effect on potatoes. Chromatographic methods were used to quantify very low pesticide levels before and after UV-C treatments (<10 µg L −1 ), while a specific method was adapted to analyse traces of GLY (0.0008–10 µg L −1 ) in recycled wastewater containing suspended particulate matter (SPM). ATR was completely eliminated from groundwater after 15 min photodegradation while 80% was removed from the turbid wastewater after 25 min. For MAL, 70–80% was removed in 25 min from the groundwater. For wastewater, the initial concentration was important for the performance of the photolytic process. An amount of 75% of GLY was eliminated after 10 min irradiation at concentrations higher than those found in natural groundwater. In wastewater, the UV-C treatment was less efficient because GLY was mainly adsorbed to SPM which obstruct the photodegradation process. Therefore, the pilot-scale UV-DS using a turbulent flow and a multiple-lamp system was performed to remove quantitatively traces of pesticides from large volumes of water, by direct photolytic oxidation, when the turbidity of the treated water was limited. Graphical Abstract: ga1 Highlights: Pilot-scale UV-C irradiation process could eliminate pesticides in ground/wastewater. A continuous flow of 40 L water for agricultural use was treated for 30 min. A chromatographic method was adapted to quantitate glyphosate traces in turbid water. More than 70% atrazine/malathion were eliminated after 25 min photolytic oxidation. The large-scale photolytic dissipation of glyphosate without catalyst was promising.